Medicolegal Essentials in Healthcare - Payne-James, Jason; Wall, Ian; Dean, Peter (Cambridge University Press, 2004)
Medicolegal Essentials in Healthcare provides a concise overview of the most clinically relevant medicolegal issues for healthcare groups in England and Wales, and is a valuable resource for medical, dental and nursing students in training as well as being a useful quick reference for practitioners in these fields. Each chapter is written by a leading expert on the subject, and as such provides up-to-date, concise, and comprehensive coverage, identifying key areas of controversy and enabling readers to put contemporary medicolegal issues into their appropriate clinical context. Key features include: • Focuses on issues of immediate relevance to healthcare professionals • Chapters written by leading experts in the field • A knowledge of medicolegal issues is of increasing importance to all healthcare professionals, as society generally becomes more litigious, and practitioners face the threat of legal claims against them